2008
DOI: 10.1016/j.gca.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reduction of Tc(VII) by Fe(II) at the solid–water interface

Abstract: Experiments were performed herein to investigate the rates and products of heterogeneous reduction of Tc(VII) by Fe(II) adsorbed to hematite and goethite, and by Fe(II) associated with a dithionite-citrate-bicarbonate (DCB) reduced natural phyllosilicate mixture [structural, ion-exchangeable, and edge-complexed Fe(II)] containing vermiculite, illite, and muscovite. The heterogeneous reduction of Tc(VII) by Fe(II) adsorbed to the Fe(III) oxides increased with increasing pH and was coincident with a second event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
163
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(176 citation statements)
references
References 76 publications
11
163
1
1
Order By: Relevance
“…In contrast, when Fe(II) is sorbed onto other mineral phases, especially iron oxyhydroxides, surface-mediated heterogeneous catalysis becomes important and reduction of Tc(VII) to Tc(IV) takes place rapidly above pH 6 (Peretyazhko et al 2008a;Peretyazhko et al 2008b;Zachara et al 2007). …”
Section: Redox Chemistrymentioning
confidence: 99%
“…In contrast, when Fe(II) is sorbed onto other mineral phases, especially iron oxyhydroxides, surface-mediated heterogeneous catalysis becomes important and reduction of Tc(VII) to Tc(IV) takes place rapidly above pH 6 (Peretyazhko et al 2008a;Peretyazhko et al 2008b;Zachara et al 2007). …”
Section: Redox Chemistrymentioning
confidence: 99%
“…28 In SRS Tank Farm waste, it is assumed that the vast majority of technetium existing in sludge solids is present as Tc(IV) and relatively insoluble, in the form of hydrated technetium dioxide (TcO 2 xH 2 O) 29 and/or co-precipitated with iron(II) sorbed onto iron(III) oxide and/or oxyhydroxide particles. 30,31 In contrast, the majority of technetium existing in salt waste is assumed to be present as Tc(VII) and relatively soluble, in the form of sodium pertechnetate (NaTcO 4 ). 29 Some portion of the soluble technetium could also be present as a Tc(IV)-chelant complex 32 or as a Tc(VII)-solvent complex, 33 but these portions are expected to be minor in most SRS waste tanks due to the very low organic content.…”
Section: Solid/liquid Phase Technetium Partitioningmentioning
confidence: 99%
“…However, when Fe(II) is adsorbed or surface precipitated on solid phases, especially oxyhydroxides of iron, a surface-mediated catalysis of Tc(VII) reduction is more rapid (Cui and Eriksen 1996a, Cui and Eriksen 1996b, Peretyazhko et al 2008a, Peretyazhko et al 2008b, Zachara et al 2007. Other experiments aimed at assessing the interaction of pertechnetate with iron sulfide minerals, such as mackinawite (FeS), pyrrhotite (Fe 7 S 8 ), and 2.17 greigite (Fe 3 S 4 ), showed that Tc(IV) has an affinity for the surface of sulfide minerals and, upon oxidation to form goethite and sulfate minerals, the…”
Section: Goethitementioning
confidence: 99%
“…The atomic structure of goethite, recently determined by Yang et al (2006), is shown in Figure 2.5. On the other hand, examining the reduced run products with X-ray absorption spectroscopy (XAS) methods (briefly described in Appendix A) has revealed that the 99 Tc-bearing phase is a separate, reduced Tc(IV) oxide phase and may not be substituting for Fe(III)-O in the host ferric oxyhydroxide phase (Burke et al 2006, Fredrickson et al 2004, Fredrickson et al 2009, Morris et al 2008, Peretyazhko et al 2008a, Watson et al 2001, Wharton et al 2000, Zachara et al 2007). In the most detailed study, Fredrickson and coworkers (Fredrickson et al 2009) found that Tc(IV)O 2 -like compounds could exist in a number of states, including physically separate phases or those that are inter-grown with Fe(III)-O compounds.…”
mentioning
confidence: 99%